2016
DOI: 10.1097/mib.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Silent Crohnʼs Disease Predicts Increased Bowel Damage During Multiyear Follow-up

Abstract: Two-thirds of patients with CD in clinical remission, while demonstrating elevated CRP, will develop bowel damage over the ensuing years, despite feeling well. These patients with silent CD are an "at-risk" group who warrant further investigation to prevent development of disease-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
2
23
1
Order By: Relevance
“…We also found that hypoalgesic CD patients were at increased risk of developing IBD-associated complications (e.g., fistulae). Each of these findings was comparable to what has been reported in other studies that attempted to evaluate silent IBD [6][7][8]10]. These results reinforce the clinical relevance of hypoalgesic IBD and the importance of improving our understanding of this condition.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that hypoalgesic CD patients were at increased risk of developing IBD-associated complications (e.g., fistulae). Each of these findings was comparable to what has been reported in other studies that attempted to evaluate silent IBD [6][7][8]10]. These results reinforce the clinical relevance of hypoalgesic IBD and the importance of improving our understanding of this condition.…”
Section: Discussionsupporting
confidence: 87%
“…If IBD patients with clinically significant disease activity do not simultaneously experience and/or report symptoms commensurate with the degree of inflammation, including abdominal pain, they are described as having silent IBD. Silent IBD is important because it has been associated with the development of more frequent and serious complications, including strictures, fistulae, and abscesses [6,7], as well as increased hospitalization [8]. As abdominal pain is one of the most frequently described and consequential symptoms in the setting of IBD [9], it is not difficult to imagine that a lack of or reduction in abdominal pain by itself during periods of significant disease activity, or "hypoalgesic IBD", can impart a tremendous risk of poor outcomes over time.…”
Section: Introductionmentioning
confidence: 99%
“…They found neither endoscopic activity nor inflammatory biomarkers (CRP or fecal protection) to be correlated with damage progression. In contrast to their results Bhattacharya and colleagues 67 found CRP to correlate to damage progression in quiescent CD.…”
Section: Clinical Implications Of Mre Indicescontrasting
confidence: 79%
“…The same group also demonstrated by using the Lémann Index that elevated CRP is independently associated with 7-fold greater worsening of the disease trajectory (OR, 6.93; 95% CI, 2.44-19.67) compared with a stable disease trajectory. 14,15 In my opinion, however, asymptomatic "Silent CD" with CRP elevation is not actually "Silent CD" because the increase in CRP, which is commonly measured in daily clinical practice, alerts the physician (especially IBD specialists) to the presence of an active lesion. We should be aware of "Real Silent CD" in which CRP levels are not elevated.…”
Section: Features Of Sb Lesions In Patients With CDmentioning
confidence: 98%